Edukasi tentang Literasi Media untuk Mencegah Disinformasi di Masa Pandemi Covid-19 - Agus Susanto; Meliyana Perwita Sari; Heni Purwantiningrum (Universitas Pahlawan Tuanku Tambusai, 2022)
Massive hoax news in the community is very disturbing efforts to control the spread of Covid-19 in Indonesia. Hoax news causes confusion and public unrest. Hoax news spread massively in the community during the Covid-19 pandemic, one of which was due to the weak ability of public media literacy in Indonesia. Overcoming this requires education about media and information literacy so that people have the ability to distinguish credible media and information. This service activity is intended to improve media and information literacy skills to prevent disinformation during the Covid-19 Pandemic in the school environment. This educational activity is carried out using the counseling method which is carried out face-to-face. Submission of material using lecture and question and answer methods. The results of the evaluation of service activities through pre-test and post-test showed an increase in knowledge about media and information literacy. Education about media and information literacy can be used as a means to empower target groups in choosing credible media and information.